Education in medieval India - Ray, Krishnalal 1923- (New Delhi : B.R. Pub. Corp. ; New Delhi, India : Distributed by D.K. Publishers' Distributors, 1984)
Study covers the period, ca. 1200-1707.
Includes bibliographical references and index.
Keywords: Education -- India -- History